PENGARUH PAYMENT POINT ONLINE BANK (PPOB) TERHADAP PERCEPATAN ALIRAN KAS ( STUDI KASUS DI PT. PLN (PERSERO) PROVINSI ACEH) - Indrayani, Indrayani (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to identify the influence of Payment Point Online Bank (PPOB) on the cash flow acceleration at PT. Perusahaan Listrik Negara (Persero). This study uses secondary data in the form of financial statements during 2017-2018 taken from the central office of PT. Perusahaan Listrik Negara (Persero) of Aceh Province. The samples used are 38 offices of PT. Perusahaan Listrik Negara (Persero) in Aceh Province. The method used to analyze the data is simple linear regression analysis. The results of this study indicate that the Payment Point Online Bank (X) influences significantly on the cash flow acceleration (Y) at PT. PLN of Aceh Province during 2017-2018.